Central bank communication on financial stability - Benjamin Born; Michael Ehrmann; Marcel Fratzscher (European Central Bank (ECB), 2011)
Central banks regularly communicate about financial stability issues, by publishing Financial Stability Reports (FSRs) and through speeches and interviews. The paper asks how such communications affect financial markets. Building a unique dataset, it provides an empirical assessment of the reactions of stock markets to more than 1000 releases of FSRs and speeches by 37 central banks over the past 14 years. The findings suggest that FSRs have a significant and potentially long-lasting effect on stock market returns, and also tend to reduce market volatility. Speeches and interviews, in contrast, have little effect on market returns and do not generate a volatility reduction during tranquil times, but have had a substantial effect during the 2007-10 financial crisis. The findings suggest that financial stability communication by central banks are perceived by markets to contain relevant information, and they underline the importance of differentiating between communication tools, their content and the environment in which they are employed.
Keywords: E44; E58; G12; 330; Central Bank; communication; event study; financial stability; Zentralbank; Geldpolitik; Kommunikation; Finanzsektor; Finanzmarkt; Ankündigungseffekt